Cone Penetration Testing in Antarctic firn: an introduction to interpretation - McCallum, A B (Journal of Glaciology, 2014)
Commercial cone penetration testing (CPT) equipment was adapted to allow penetrative testing in hard polar firn to depths of 10 m. The apparatus is hydraulically driven, rate-controllable and able to penetrate firn with a resistance of 10MPa. It can be mounted on many types of typical polar vehicles, requiring connection to only hydraulics and 12V electricity. Data recorded include both cone tip resistance and sleeve friction, a parameter not previously examined through such testing. This paper describes the development and calibration of the equipment and examines factors including snow density, penetration rate and cone size and shape that are shown to affect CPT interpretation. CPT can be used efficiently in polar environments to potentially provide estimates of physical parameters in hard firn to substantial depth.